2015
DOI: 10.1007/s00520-015-2729-2
|View full text |Cite
|
Sign up to set email alerts
|

Early percutaneous endoscopic gastrostomy and nutritional supplementation for patients with head and neck cancer: an Italian survey of head and neck radiation oncologists

Abstract: Although some studies agree that a reactive approach should be preferred to an early endoscopic percutaneous gastrostomy placement, firm evidences and a clear consensus are still lacking. This survey shows a wide agreement about both timing and criteria for endoscopic percutaneous gastrostomy placement; however, the management of nutritional supplementation in head and neck cancer patients appears to be still widely variable and to deserve more focused studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…41 Prophylactic PEG was more common than reactive PEG in abroad, with rate of catheterization 51.75% and 13.5%, respectively. 49 Most Chinese patients cannot accept PEG because they consider it as an invasive procedure, so nutritional therapy mostly presents in the form of HEN. It was suggested that PEG may not be considered before the radiation dose reaches 30 Gy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Prophylactic PEG was more common than reactive PEG in abroad, with rate of catheterization 51.75% and 13.5%, respectively. 49 Most Chinese patients cannot accept PEG because they consider it as an invasive procedure, so nutritional therapy mostly presents in the form of HEN. It was suggested that PEG may not be considered before the radiation dose reaches 30 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 A survey implied that 82.1% of doctors thought that prophylactic PEG was not necessary, but 88.1% agreed that nutritional consultation should be a routine step in the radiotherapy process. 49 Most Chinese patients cannot accept PEG because they consider it as an invasive procedure, so nutritional therapy mostly presents in the form of HEN. It has been found that PLT of HEN patients with BMI < 24 kg/m 2 before CCRT increased significantly at the end of radiotherapy, and both WBC and PLT were higher than those of the control group at the end of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The survey was prepared on the Survey Monkey online interface (www.SurveyMonkey.com). Starting from 1 April 2014 personalized e-mail invitations with direct links to the survey were sent to the Directors of the selected Italian centres of Otolaryngologists (the same questionnaire had sent to 106 Italian centres of radiation oncology) [29]. No compensation was offered to participating.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we report the results of our survey, the first Italian survey directed to Otolaryngologists about the management of nutritional support in patients with HNC. This survey represents the second step of a project aimed to search for a point of view of experts dedicated to HNC (radiotherapists and otolaryngologists), in order to establish common guidelines [29].…”
Section: Introductionmentioning
confidence: 99%